Synthesis of Review of Corporate Governance of State-Owned Enterprises in Burkina Faso, Mali, and Mauritania - Bouri, Mazen; Nankobogo, Francois; Frederick, Rich (World Bank, Washington, DC, 2017)
This synthesis paper is based on a review of three countries in West Africa-Burkina Faso, Mali, and Mauritania where state owned enterprises (SOEs) continue to play an important role and Governments have embarked on a number of public sector reforms are intended to have a positive impact on SOEs. SOE governance practices and problems are having strong similarities in all of the countries reviewed. These commonalities can be ascribed to the fact that all of the countries are transitioning from centrally controlled economic and political traditions to more liberal economies and to a more democratic government. All are facing challenges with implementing the legal structures left behind from colonial times. The data that is available shows that wholly-owned and state controlled SOEs under perform. Many are technically insolvent and survive only through government support. Their performance is not only poor in the financial area but also in the provision of needed social services. The country studies link the poor performance of SOEs, in particular wholly-owned SOEs, to their governance practices. Long-lasting reforms are not simply a matter of plugging holes in the legislative or institutional framework. Corporate governance is the result of a complex interplay of law, practice, institutions and culture. Action plans need to take into account incentives and the political, social and cultural context of corporate governance in the country in addition to the legal framework. Indeed, SOE governance is a system and making it work better requires a systems approach. Most reform plans in the past have focused on one or another element of SOE governance, which might explain why many have fallen short of hopes and expectations. Systems approaches, on the other hand, are important in complex organizations (such as SOEs) whose success depends upon the interaction and cooperation of other organizations and institutions. This synthesis paper presents the objectives and the methodology used in carrying out the reviews followed by a discussion of the features and importance of SOEs in each of the countries studied. It then segues into a discussion on the performance of SOEs which is supplemented by case studies of both successful and unsuccessful SOEs and key lessons learned the paper then presents the current Government initiatives for reform and the remaining challenges and recommendations. The paper concludes with suggestions on how to implement the recommendations based on examples from other countries that have embarked on comprehensive governance reforms for the SOE sector.